The study of human bone marrow derived stem cells proliferation and multi-lineage differentiation in various spatial parameter microwells - Tan, Wei Ling (2015)
Stem cells-scaffold constructs were widely applied in tissue engineering, in which pore size and porosity are important parameters of traditional scaffold and 3D customized device for regenerative medicine. To optimize the pore shapes and sizes, a diverse array of environmental factors were prepared for studying stem cell fate. In this study, we investigated influence of geometrical cue in manipulating cell fate control for long term cell confinement. Four fundamental shapes (rectangle, square, circle and triangle) with four specific surface areas of 657.7 μm2, 1208.7 μm2, 1796.7 μm2 and 2312.1μm2 of microwells have been fabricated. The microstructures were characterized by SEM. Interestingly, high cell seeding efficiency was observed regardless of shape and size factors of microwell arrays. Cell proliferation profile revealed constant cell cycle progression under long term culture inside the microwells. Immunocytochemical staining and biochemical analysis showed larger size (size ratio of 1: 2) of the microwells were able to promote adipocytes formation while smaller size (size ratio of 1: 2) of the microwells were able to differentiate into chondrocytes. Furthermore, rectangular shapes of the microwells were able to induce fibroblasts formation. Collectively, this preliminary research provides a screening of board range of physical parameters of size and shape factors precise control of local environment that promotes proliferation and differentiation of cells in which play a vital role in gaining insight into future research studies and clinic application in tissue regeneration.